2023
DOI: 10.1111/age.13365
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the discovery of genetic elements underlying longissimus dorsi muscle growth and development in the pig

Qingjie Zeng,
Zhi‐Qiang Du

Abstract: As a major source of protein in human diets, pig meat plays a crucial role in ensuring global food security. Key determinants of meat production refer to the chemical and physical compositions or characteristics of muscle fibers, such as the number, hypertrophy potential, fiber‐type conversion and intramuscular fat deposition. However, the growth and formation of muscle fibers comprises a complex process under spatio‐temporal regulation, that is, the intermingled and concomitant proliferation, differentiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…The longissimus dorsi (LD) muscle is a crucial component of animal muscle anatomy, closely associated with the growth and development of skeletal muscles and the intramuscular fat content in animals [ 33 ]. Studies have demonstrated that bovine LD muscles contain a high proportion of fast-twitch (Type II) fibers, which have larger diameters than slow-twitch (Type I) fibers, favoring muscle hypertrophy [ 34 ]. Hepatocyte growth factor (HGF) is present in skeletal muscles and promotes skeletal muscle regeneration by activating quiescent satellite cells.…”
Section: Discussionmentioning
confidence: 99%
“…The longissimus dorsi (LD) muscle is a crucial component of animal muscle anatomy, closely associated with the growth and development of skeletal muscles and the intramuscular fat content in animals [ 33 ]. Studies have demonstrated that bovine LD muscles contain a high proportion of fast-twitch (Type II) fibers, which have larger diameters than slow-twitch (Type I) fibers, favoring muscle hypertrophy [ 34 ]. Hepatocyte growth factor (HGF) is present in skeletal muscles and promotes skeletal muscle regeneration by activating quiescent satellite cells.…”
Section: Discussionmentioning
confidence: 99%
“…Researching the regulation mechanism of muscle development will not only help to increase meat yield, but also help to improve meat quality. Muscle development is a complicated process, including the formation of muscle fibers in embryonic period, the muscle fibers development after birth, and muscle regeneration in adulthood [ 2 ]. The embryonic stage is the most important, the number of muscle fibers is generally fixed at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…Pork is the most widely consumed meat in the world and plays a crucial role in ensuring global food security [1,2]. The deposition and composition of lipids in pork affect its sensory and nutritional quality, with triglycerides (TG) being the main form of lipid storage [3].…”
Section: Introductionmentioning
confidence: 99%